Smith, Lloyd. A video clip on the use of snow plows in Heart's Content. - Wilson, Lisa (2013)
In the 1950s a bulldozer was used to clear snow during the winter in Heart's Content. Image provided by Lloyd and shows Main street being cleared by a bulldozer in 1959.